PENGEMBANGAN PERTANIAN ORGANIK DI INDONESIA (Forum Penelitian Agro Ekonomi, 2016)
Awareness of the dangers posed by the use of synthetic chemicals in farming attracts attention at both the producers and consumers. Most consumers will choose safe food ingredients for better health and it drives increased demand for organic products. Healthy, environmentally friendly life-style becomes a new trend and has been institutionalized internationally which requires assurance that agricultural products should be safe for consumption (food safety attributes), high nutrient content (nutritional attributes) and environmentally friendly (eco-labeling attributes).  Indonesia has a great potential to compete in the international market, but it should be implemented gradually. This is because of many comparative advantages, i.e. (i) there are large land areas available for organic  farming; (ii) technology to support organic farming is available such as composting, no-tillage planting, biological pesticides, among others. Although the government has launched various policies on organic agriculture such as "Go Organic 2010”, but the development of organic farming in the country is relatively slow. This situation is due to various problems such as market constraints, consumers’ interest, relatively expensive organic products certification for small farmers, and lack of farmers’ partnership with private companies. However, interest for organic farming has grown and it is expected to have positive impacts on the development of organic agriculture in Indonesia.